ขอบเขตพื้นที่ที่ได้รับอิทธิพลจากการสูบน้ำ และการกระจายตัวทางอุทกธรณีเคมีในน้ำ บาดาล บริเวณรอบเหมืองทองทุ่งคำ จังหวัดเลย - ณรงค์พนธ์ สำแดง (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
In this study, the prospective geochemical distribution and capture zone delineation in groundwater around the Tungkum Gold Mine area, Loei province, Thailand. The observed data was conducted by the previous studies, consisting of the observed geochemical data from 24 wells in 1996 and 30 wells in 2012. To investigate the geochemical distribution, the multivariate statistical analyses, consisting of 1) Cluster analysis 2) Friedman’s test, 3) Mann-Whitney test, and 4) Spearman correlation were performed. According to CA method, the result showed that the observation wells were divided into 2 groups, responsible to the distance from the tailing dam: 1) observation wells were laid near the mine tailings dam not < 1500 meter and 2) observation wells were laid far from the tailings dam > 1500 meter. The Friedman’s test showed that well P1, located approx. 528 meters downstream from the tailings dam, had the highest mean rank value of 40.20, while well CGW30, located approx. 3,781 meters downstream from the tailing dam, had the lowest mean rank value of 15.40. The Mann-Whitney test revealed that the concentration of trace elements in groundwater appeared to be in the descending order: Arsenic (As), Zinc (Zn), Lead (Pb), and Copper (Cu). Futhermore, the Spearman correlation showed that correlation coefficients values of four elements presented in the following order: As (-.443), Zn (- .254), Pb (-.103), and Cu (-.094). The statistical analysis can conclude that the relationships between trace elemental concentrations in the groundwater samples and distance of a sampling site from the mine tailings dam were negative relationship. Eight trace elements (i.e, As, Cd, Cu, Hg, Fe, Mn, Se, Pb, and Zn) that were recorded during 2012 were determined by used heavy metal pollution index (HPI), the result showed that the wells with HPI > 100 were approx. 27% of the observation wells, consisting of CGW7, CGW9, CGW10, CGW11, CGW13, CGW19, CGW26, and CGW27. Finally, a Visual MODFLOW FLEX showed that particles generated move not more than 500 meters around tailing dam and a capture zone delineation from pumping wells appeared to be not interfered by mining area, including the tailing dam, but the pumping well, JJ1053, was laid near CGW19 should be further monitored for water quality before use.